Incidence Of Kidney Stones in Diabetic and Non-Diabetic Patients on Ultrasound: Kidney Stones in Diabetic and Non-Diabetic Patients - Akhtar , Dania; Yousaf Farooq, Syed Muhammad; Khalid , Tooba; Yaseen, Khadija; Nazir, Ayesha; Miraj , Kashaf; Chaudhary , Zaira (Pakistan Journal of Health Sciences, 2022)
The incidence of urinary stone disease has shown a steep rise in recent decades in all industrialized countries, as did the incidence of obesity, the metabolic syndrome, and type 2 diabetes. Objective: To determine the incidence of nephrolithiasis in diabetic and non-diabetic patients. Methods: A descriptive study was conducted at University of Lahore’s Ultrasound Centre. 300 patients of age group 19 to 85 were enrolled in this study with convenient sampling technique. Out of 300 patients 184 were males and 116 were females and half of them were with the history of diabetes and remaining were normal. Results: Out of 300 patients 150 (50%) patients were with the history of diabetes and 150 (50%) were normal. 184 (61.3%) males and 116 (38.7%) females were enrolled in this study. Out of 300 patients 177(59.0%) patients were obese and 113 (41%) were normal. In this study different age groups were selected. Mean ± SD value of age was 40.796 ± 16.110. Out of 150 diabetic patients, 120 (80.0%) were diagnosed with renal stones. Conclusions: It is concluded that the patients with the history of diabetes are more likely to develop kidneys stones as compared to non-diabetic patients. Males are more likely to develop kidney stones than females